IMPLEMENTASI INTERNET OF THINGS (IoT) DALAM SISTEM PENGONTROLAN SUHU OTOMATIS BERBASIS MIKROKONTROLER PADA ALAT PROOFER UNTUK PENGEMBANG ADONAN ROTI DI UMKM PIZZA OEI OEI AND PATISSERIE - Nelson Silitonga; Dian Kurnia; Elvri Melliaty Sitinjak; Sari Farah Dina; Abdillah; Golfrid Gultom; Harmileni; Rycce Sylviana Pratikha; Yanto; Muhammad Iqbal Harapan Muslim Siregar (Journal of Golden Generation Abdimas, 2025)
Implementation of Internet of Things (IoT) technology and microcontrollers as an automatic temperature control system on tools for proofing bread dough at the Oei Oei Pizza and Patisserie Micro, Small, and Medium Enterprise (MSMEs). The primary issue faced by partners was temperature instability during the dough fermentation process, leading to inconsistent product quality. The implementation method included problem identification, tool design and construction, implementation at partner locations, and mentoring and evaluation. The results of the activity showed that the tool can help IoT-based systems maintain stable fermentation temperatures, improve dough quality consistency, and increase production efficiency. This initiative also has a positive impact on increasing partners' capacity to utilize appropriate technology.